2019
DOI: 10.9734/ajfar/2019/v4i130045
|View full text |Cite
|
Sign up to set email alerts
|

Culture of Moina macrocopa Using Different Types of Organic Wastes

Abstract: Moina macrocopa was cultured with different animal manures (chicken manure, pig manure and cow manure) and food waste to determine the impact of these food sources on its mass production. All diets were provided at five different concentrations: 500, 1000, 2500, 5000 and 10000 ppm. Gross and net reproductive rates were higher in 1000 ppm concentration of food waste medium and the highest average population growth was obtained of about 9 org mL-1 whereas pig manure treatment showed the lowest among all the cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
(22 reference statements)
2
0
0
Order By: Relevance
“…(Roustaian et al, 2001) reported similar declines in the fatty acid composition of the larval freshwater prawn, Macrobrachium rosenbergii , as well as the use of caloric‐rich lipids to sustain swift morphology and consistent swim‐like behaviour correlated with food selection. These results were supported by research in P. pelagicus larvae, which decreased the level of EPA, DHA and ARA, suggesting that the HUFAs requirement decreased when the larval stage increased (Kabery et al, 2019). This form of the metabolism of fatty acids has also been reported for larvae of marine crustaceans, S. serrata and for species with life‐cycle close to that of S. olivacea , the reductions in tissue lipids during ontogeny can be related to larval buoyancy (Holme et al, 2009; Vadher, 2020).…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…(Roustaian et al, 2001) reported similar declines in the fatty acid composition of the larval freshwater prawn, Macrobrachium rosenbergii , as well as the use of caloric‐rich lipids to sustain swift morphology and consistent swim‐like behaviour correlated with food selection. These results were supported by research in P. pelagicus larvae, which decreased the level of EPA, DHA and ARA, suggesting that the HUFAs requirement decreased when the larval stage increased (Kabery et al, 2019). This form of the metabolism of fatty acids has also been reported for larvae of marine crustaceans, S. serrata and for species with life‐cycle close to that of S. olivacea , the reductions in tissue lipids during ontogeny can be related to larval buoyancy (Holme et al, 2009; Vadher, 2020).…”
Section: Discussionsupporting
confidence: 57%
“…These results were supported by research in P. pelagicus larvae, which decreased the level of EPA, DHA and ARA, suggesting that the HUFAs requirement decreased when the larval stage increased (Kabery et al, 2019). This form of the metabolism of fatty acids has also been reported for larvae of marine crustaceans, S. serrata and for species with life-cycle close to that of S. olivacea, the reductions in tissue lipids during ontogeny can be related to larval buoyancy (Holme et al, 2009;Vadher, 2020).…”
Section: Ta B L Esupporting
confidence: 63%